2022
DOI: 10.1038/s41586-021-04306-4
|View full text |Cite
|
Sign up to set email alerts
|

Polarized phonons carry angular momentum in ultrafast demagnetization

Abstract: Magnetic phenomena are ubiquitous in our surroundings and indispensable for modern science and technology, but it is notoriously difficult to change the magnetic order of a material in a rapid way. However, if a thin nickel film is subjected to ultrashort laser pulses, it can lose its magnetic order almost completely within merely femtosecond times [1]. This phenomenon, in the meantime also observed in many other materials [2-7], has connected magnetism with femtosecond optics in an efficient, ultrafast and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 77 publications
5
59
1
Order By: Relevance
“…Analyzing the properties of these parameters, in particular their dependence on spin-orbit coupling, we find that even in bcc Fe the leading term which is responsibla for the exchange of angular momentum between the spin system and the lattice is a Dzyaloshiskii-Moriya-type interaction, which emerges due to the symmetry breaking distortion of the lattice. Our findings, hence, stress the importance of relativistic effects for the transfer of angular momentum from magnonic excitations to circularily polarized phonons [5,[7][8][9][10]…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Analyzing the properties of these parameters, in particular their dependence on spin-orbit coupling, we find that even in bcc Fe the leading term which is responsibla for the exchange of angular momentum between the spin system and the lattice is a Dzyaloshiskii-Moriya-type interaction, which emerges due to the symmetry breaking distortion of the lattice. Our findings, hence, stress the importance of relativistic effects for the transfer of angular momentum from magnonic excitations to circularily polarized phonons [5,[7][8][9][10]…”
supporting
confidence: 61%
“…In certain ferrimagnets, a single laser pulse can switch the magnetization orientation on a sub-picosecond time scale [2], due to the exchange of spin angular momentum between the two magnetic sublattices [3,4]. However, recent work on ultrafast demagnetization in ferromagnets has demonstrated that angular momentum can also be transferred from the spin system to the lattice on similar time scales [5]. In the lattice, the spin angular momentum is absorbed in terms of phonons carrying the angular momentum till -on larger times scales -the macroscopic Einstein-deHaas effect sets in [6].…”
mentioning
confidence: 99%
“…This was observed directly in silicon by Harb et al (2008). Spin-lattice coupling has also recently been interrogated from the lattice perspective using UED (Tauchert et al, 2022;Windsor et al, 2021).…”
Section: Examples From Literaturementioning
confidence: 90%
“…Over the past two decades, ultrafast electron diffraction (UED) 54,55 has evolved into a highly sensitive technique to probe structural phase transitions 23,[36][37][38][39][40][41][42][43][44][45]56 and transi- ent phonon populations 33,57,58 on femtosecond time scales. State-of-the-art time-resolved electron diffraction instrumentation typically uses large-diameter beams (>100 ”m spot size) for averaged probing of CDW amplitudes, addressing a compromise between a small spot size and sufficient reciprocal-space resolution.…”
Section: Ultrafast High-coherence Nanobeam Diffractionmentioning
confidence: 99%